1994
DOI: 10.1021/jm00047a001
|View full text |Cite
|
Sign up to set email alerts
|

L-735,524: The Design of a Potent and Orally Bioavailable HIV Protease Inhibitor

Abstract: A series of HIV protease inhibitors possessing a hydroxylaminepentanamide transition state isostere have been developed. Incorporation of a basic amine into the backbone of the L-685,434 (2) series provided antiviral potency combined with a highly improved pharmacokinetic profile in animal models. Guided by molecular modeling and an X-ray crystal structure of the inhibited enzyme complex, we were able to design L-735,524. This compound is potent and competitively inhibits HIV-1 PR and HIV-2 PR with Ki values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
154
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(157 citation statements)
references
References 5 publications
2
154
0
1
Order By: Relevance
“…The oral bioavailability of functional MDL 74,695 in rats when formulated in DMSO was low but comparable to that reported for Roche's saquinavir measured in man (Williams et al, 1992), although both were less than indinavir measured in rats (Vacca et al, 1994) and much less than ritonavir in several species (Kempf et al, 1995). This may be due to low absorption or first-pass metabolism through the portal circulation.The poor bio-availability of MDL 74,695 was reflected in its relatively low peak plasma concentration and the period for which protective levels were maintained.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The oral bioavailability of functional MDL 74,695 in rats when formulated in DMSO was low but comparable to that reported for Roche's saquinavir measured in man (Williams et al, 1992), although both were less than indinavir measured in rats (Vacca et al, 1994) and much less than ritonavir in several species (Kempf et al, 1995). This may be due to low absorption or first-pass metabolism through the portal circulation.The poor bio-availability of MDL 74,695 was reflected in its relatively low peak plasma concentration and the period for which protective levels were maintained.…”
Section: Discussionsupporting
confidence: 70%
“…Despite problems with bio-availability, a number of these proteinase inhibitors have been investigated in clinical trials and some, including the Merck compound indinavir (Crixivan; MK-639; L-735,524) (Vacca et al, 1994;Dorsey et al, 1994), the Roche compound saquinavir (Invirase; Ro-31-8959) (Roberts et al, 1990;Craig et al, 1991) and the Abbott compound ritonavir (Norvir; ABT-538) (Kempf et al, 1995), have shown efficacy, particularly in combination with reverse transcriptase (RT) inhibitors (Vella, 1994(Vella, , 1995Kitchen et al, 1995;Danner et al, 1995;Markowitz et al, 1995a;Collier et al, 1996;Schapiro et al, 1996). Recently saquinavir, indinavir and ritonavir have all been given accelerated approval for use in AIDS patients by the US Food and Drug Administration (Anon, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…HIV protease is a virus-encoded enzyme that is essential for processing of Gag and Gag-Pol into structural proteins and replication enzymes required for virion production (4). A number of potent HIV-1 protease inhibitors including A-77003, ABT-538, saquinavir, MK-639, SC52151, and BMS-186318 have been described (5)(6)(7)(8)(9)(10)(11)(12)(13). Several of these have been recently tested in human clinical trials and demonstrated significant reductions in viral load (14,15).…”
mentioning
confidence: 99%
“…2,3 Our research group has investigated approaches to obtain indans from 1,2-dihydronaphthalenes, using a thallium(III)-promoted ring contraction reaction. [4][5][6][7][8][9] During these studies, we found that a side chain at the double bond has a strong influence in the reaction pathway.…”
Section: Introductionmentioning
confidence: 99%